1999
DOI: 10.1046/j.1442-2042.1999.06310.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pheochromocytoma using [123I]‐ compared with [131I]‐metaiodobenzylguanidine scintigraphy

Abstract: Background: Patient with pheochromocytoma (PCT) cannot be cured without operation, therefore, preoperative determination of the localization of PCT should be performed accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 2 publications
2
87
0
2
Order By: Relevance
“…Despite comparable results of I-MIBG scintigraphy in PCC/PGL detection [34], the lower sensitivity of 131 I-MIBG scintigraphy observed in this study could still be 18 F-FDG PET/CT was considered true positive, the specificities of all three modalities are thus, by definition, 100 % I for imaging with current gamma cameras, which contribute to poorer target-to-background ratio, and therefore possibly lower detection rate. Other factors, such as different biological properties among patients or presence of MIBGconfounding therapy, may also contribute to these discrepancies.…”
Section: F-fdg Pet/ct Images Although 68mentioning
confidence: 50%
“…Despite comparable results of I-MIBG scintigraphy in PCC/PGL detection [34], the lower sensitivity of 131 I-MIBG scintigraphy observed in this study could still be 18 F-FDG PET/CT was considered true positive, the specificities of all three modalities are thus, by definition, 100 % I for imaging with current gamma cameras, which contribute to poorer target-to-background ratio, and therefore possibly lower detection rate. Other factors, such as different biological properties among patients or presence of MIBGconfounding therapy, may also contribute to these discrepancies.…”
Section: F-fdg Pet/ct Images Although 68mentioning
confidence: 50%
“…However, the sensitivity of CT for extra-adrenal pheochromocytoma is lower than that for adrenal pheochromocytoma (82% vs. 94%) (11). The sensitivity and specificity of MIBG scintigraphy is reported to be 87.4% and 99%, respectively (19). MIBG scintigraphy is the most valuable tool in detection of extra-adrenal pheochromocytoma and its metastases, especially when CT and MRI findings are negative.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies demonstrated a poor overall sensitivity of 123 I-MIBG scintigraphy in SDHB-related PPGLs (,50%) (24,25). Similar to 123 I-MIBG, several PET tracers specifically target catecholamine synthesis, storage, and secretion pathways including 18 F-fluorodihydroxyphenylalanine and 18 F-fluorodopamine. Kaji et al showed that 18 F-fluorodihydroxyphenylalanine PET is superior to 123 I-MIBG scintigraphy in the context of von HippelLindau syndrome (26).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, specificities of 123 I-MIBG scintigraphy range between 70% and 100% for pheochromocytomas and 84% and 100% for paragangliomas, whereas sensitivities range between 85% and 88% and 56% and 76%, respectively (14)(15)(16)(17). Physiologic uptake of 123 I-MIBG by normal adrenal glands can give false-positive results or obscure small lesions (18)(19)(20). The sensitivity appears to be lower for extraadrenal, metastatic, recurrent, and certain hereditary PPGLs (14,16,(21)(22)(23)(24).…”
mentioning
confidence: 99%